ChemInform Abstract: Clindanones A and B and Cladosporols F and G, Polyketides from the Deep‐Sea Derived Fungus Cladosporium cladosporioides HDN14‐342. Issue 52 (6th December 2016) - Zhang, Zhenzhen; He, Xueqian; Liu, Congcong; Che, Qian; Zhu, Tianjiao; Gu, Qianqun; Li, Dehai
Abstract: Cladosporol G (I), together with another three new tetralone derivatives and three known biogenetically related polyketides, is isolated from title deep‐sea derived fungus and is shown to have the best cytotoxic activity against HeLa cells with an IC50 value of 3.9 μM.